Comparison between Demand and Supply of Some Ecosystem Services in National Parks: A Spatial Analysis Conducted Using Italian Case Studies - Marino, Davide; Palmieri, Margherita; Marucci, Angelo; Tufano, Massimo (Conservation, 2021)
In recent decades, modeling approaches of ecosystem services (ES) have been used extensively at the international level, providing useful tools during the decision-making process by integrating both physical and economic information, thus improving its management. The relationship between supply and demand may impact social welfare: for example, a deficit in ES could negatively influence demand (either potential or effective). For this reason, the relational study between supply and demand is necessary for the sustainable management of natural resources; particularly since the demand for some ES must be fulfilled not only on a local scale but also globally (as in the case of regulatory ES). This paper proposes an ES analysis framework that links the flow of services (supply) generated by the interaction between natural, human and social capital with consumption (demand) connected to potential beneficiaries. Specifically, we analyze three ES: Forage production, regulation of local climate (PM10), and carbon sequestration in three national parks (Aspromonte National Park, Circeo National Park, and Appennino Tosco Emiliano National Park). The use of synthetic (biophysical) indicators, on a spatial basis, made it possible to quantify the supply and demand of specific catchments with the aim of accounting for the surplus/deficit through the calculation of the ES supply and demand ratio (ESDR). In fact, sustainable land management requires a balance between supply and demand in relation to the different needs of the stakeholders and local community. The relationship between supply and demand of ES can help identify resource use trade-offs, thus rendering the achievement of management and protection objectives more efficient. Lastly, through the use of monetary coefficients, it was possible to calculate the benefits of increasing the awareness of public decision-makers of ES’s value and the importance of implementing integrated strategies for environmental protection and enhancement.